2011
DOI: 10.2169/internalmedicine.50.5101
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Neuromelanin-Positive Nigral Volume in Patients with MSA, PSP and CBD

Abstract: Objective Diseases presenting extrapyramidal symptoms are accompanied by nigral cell loss. In the previous study, we demonstrated the reduction of the neuromelanin-positive volume of substantia nigra (SN) pars compacta (SNc) in patients with Parkinson's disease (PD) using 3-Tesla MRI. In the present study we investigated the neuromelanin-positive SNc volume in patients with the other parkinsonian disorders including multiple system atrophy (MSA), progressive supranuclear palsy (PSP) and corticobasal degenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 23 publications
2
41
1
3
Order By: Relevance
“…More recently, Kashihara et al [18] reported that reduced volume of neuromelanin-positive SNc was found in patients with MSA using neuromelanin imaging based on the signal decrease of SNc compared with that of surrounding brain tissue. However, no report in the relevant literature has described neuromelanin imaging regarding the LC in MSA, although MSA patients exhibit autonomic symptoms and neuronal loss and gliosis in the SNc and LC (more predominantly in the latter) [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, Kashihara et al [18] reported that reduced volume of neuromelanin-positive SNc was found in patients with MSA using neuromelanin imaging based on the signal decrease of SNc compared with that of surrounding brain tissue. However, no report in the relevant literature has described neuromelanin imaging regarding the LC in MSA, although MSA patients exhibit autonomic symptoms and neuronal loss and gliosis in the SNc and LC (more predominantly in the latter) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal loss and gliosis occur in the SNc of MSA patients, but in a more delayed fashion compared to that in PD [3], which might account for the discrepant results from a decreased contrast ratio of the SNc in MSA in a previous study [18]. In the early stage of PD, the contrast ratio of SNc mi decreased more markedly than that of SNc me .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sasaki and colleagues reported that both LC and SN can be imaged by using a T 1 -weighted turbo spin echo (TSE) sequence [8]. Other groups have also successfully applied similar spin echo techniques to study the LC and/ or SN [4,5,[9][10][11][12]. The size of the LC (a rod-shaped structure approximately 2-mm wide and 15-mm long) [13,14] dictates the need for an acquisition with high spatial resolution.…”
Section: Introductionmentioning
confidence: 99%